-7+6x=-2x-71

Simple and best practice solution for -7+6x=-2x-71 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+6x=-2x-71 equation:



-7+6x=-2x-71
We move all terms to the left:
-7+6x-(-2x-71)=0
We get rid of parentheses
6x+2x+71-7=0
We add all the numbers together, and all the variables
8x+64=0
We move all terms containing x to the left, all other terms to the right
8x=-64
x=-64/8
x=-8

See similar equations:

| 3x+12=12+25+50 | | 6b+8=9b-4 | | 4v-6+v=-6 | | -8x+2(8x-9)=7x+5(-6x+3) | | −10x−1=11−9x | | -2/4p+1/4=-3/10 | | 8x+4=4x−12x+12 | | 5x+7=2x/2 | | 5-(2t-6)=-19 | | 11-a1=-23 | | +5+7x=-10+4x | | 3m+21+2m=24 | | 2x-18+8=x+2 | | 1y²+1y²+y²=0 | | 4–2x=5+7x | | 5x-3x+14=40 | | x+2=2x-18+8 | | 3(x+7)-2=10x+5 | | 8-x=7-5x | | -x+3x=16 | | 2b–9=3 | | 60=5(7x-2x | | 5d+7=42 | | 2x+23+x+13=90° | | 1/2(6+2)-x=x+-1/2(6+2) | | 2(4x-3)=4x-30 | | -12+52=-5(x+3) | | e-(12-e)=38 | | -9(x-2)=108 | | d-13.49=4.11 | | 7(x-2)-7=8(x-4) | | 7+4x+5x+2=90 |

Equations solver categories